2012
DOI: 10.1124/mol.112.078063
|View full text |Cite
|
Sign up to set email alerts
|

OX1 Orexin/Hypocretin Receptor Signaling through Arachidonic Acid and Endocannabinoid Release

Abstract: We showed previously that OX 1 orexin receptor stimulation produced a strong 3 H overflow response from [ 3 H]arachidonic acid (AA)-labeled cells. Here we addressed this issue with a novel set of tools and methods, to distinguish the enzyme pathways responsible for this response. CHO-K1 cells heterologously expressing human OX 1 receptors were used as a model system. By using selective pharmacological inhibitors, we showed that, in orexin-A-stimulated cells, the AA-derived radioactivity was released as two dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
78
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(89 citation statements)
references
References 61 publications
3
78
0
Order By: Relevance
“…We have recently shown that the endocannabinoid 2-AG is strongly produced and released in OX 1 receptor signaling, and that this 2-AG is able to act as a potent paracrine messenger via CB 1 receptors (Turunen et al, 2012). This, together with the studies in the CNS, suggests that 2-AG production is an important signal in orexin-mediated regulation of synaptic transmission.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…We have recently shown that the endocannabinoid 2-AG is strongly produced and released in OX 1 receptor signaling, and that this 2-AG is able to act as a potent paracrine messenger via CB 1 receptors (Turunen et al, 2012). This, together with the studies in the CNS, suggests that 2-AG production is an important signal in orexin-mediated regulation of synaptic transmission.…”
Section: Introductionmentioning
confidence: 87%
“…CHO-hCB 1 cells, expressing human CB 1a receptor (Grimsey et al, 2010), were a kind gift from Dr. Michelle Glass (University of Auckland, Auckland, New Zealand) via Drs. Jarmo Laitinen and Juha Savinainen (University of Eastern Finland, Kuopio, Finland); the culture conditions for these have been described (Turunen et al, 2012). For Western blotting (WB) experiments, the cells were cultured on six-well plates (9.6-cm 2 well bottom area; Greiner Bio-One GmbH, Frickenhausen, Germany); for the luciferase assays, on either 24-or 96-well plates (Greiner Bio-One GmbH); and for the receptor binding experiments, on cell culture dishes (56-cm 2 bottom area) or 48-well plates (Greiner Bio-One GmbH).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…25 In an in vitro study, it was demonstrated that the coexpression of CB1 and OX1 receptors results in a higher potentiation of ERK signalling, possibly because of heterodimerization/oligomerization of these two receptors. 26 Recently, however, it was also shown that 2-AG produced and released through the activation of OX1 receptor acts as both a paracrine and autocrine messenger via CB1 receptors, 23,27 thus possibly explaining the above-mentioned findings in the rat dorsal raphe nucleus and periaqueductal gray, as well as the potentiation of ERK phoshorylation that follows OX1/CB1 receptor coexpression. These data suggest the involvement of 2-AG and CB1 receptors not only in orexin-A release but also in orexin-mediated regulation of synaptic transmission.…”
Section: Leptin-mediated Hypothalamic Ecb/orexin Interactionsmentioning
confidence: 97%
“…They have a pivotal role in the regulation of sleep/wakefulness, pain, reward and appetite, and a recent study demonstrates their interaction with the ECS. 23 Interestingly, in the rat dorsal raphe nucleus, orexin-Bmediated inhibition of glutamate release can be due to 2-AG release and subsequent activation of CB1 receptors on glutamatergic presynaptic terminals. 24 In the rat periaqueductal gray, orexin-A-induced analgesic responses rely on a similar 2-AG/CB1-mediated 'retrograde' inhibition of Y-aminobutyric acid (GABA) release.…”
Section: Leptin-mediated Hypothalamic Ecb/orexin Interactionsmentioning
confidence: 99%